2018
DOI: 10.1021/acs.orglett.8b03610
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Arenesulfonyl Fluorides via Sulfuryl Fluoride Incorporation from Arynes

Abstract: Transition-metal-free multicomponent reactions involving aryne precursors, secondary amines, and sulfuryl fluoride are reported herein. Zwitterionic intermediates formed from the reaction of arynes with amine nucleophiles can capture SO2F2 under mild conditions, offering a novel and practical protocol for the synthesis of 2-dialkyl-, 2-alkylaryl-, or 2-diarylamino-substituted arenesulfonyl fluoride derivatives in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 90 publications
0
24
0
1
Order By: Relevance
“…In 2018, Kim reported that zwitterion 31 could be trapped with sulfuryl fluoride to generate structurally diverse 2-amino arenesulfonyl fluoride 32d. 45 Later in 2019, Tian showed that in the presence of organic halides [CCl 4 , Nchlorosuccininmide (NCS), CBr 4 , N-bromosuccinimide (NBS), N-iodosuccinimide (NIS)], can trap zwitterionic intermediate 31 to provide the corresponding 2-chloro, 2bromo, 2-iodo aniline derivatives 32e. 46 Biju and co-workers reported that MCRs of arynes with tertiary aromatic amines and carbon dioxide formed zwitterionic intermediate 33, which could undergo either N→O alkyl or aryl group migration to generate anthranilic acid derivatives (Scheme 12).…”
Section: Account Syn Lettmentioning
confidence: 99%
“…In 2018, Kim reported that zwitterion 31 could be trapped with sulfuryl fluoride to generate structurally diverse 2-amino arenesulfonyl fluoride 32d. 45 Later in 2019, Tian showed that in the presence of organic halides [CCl 4 , Nchlorosuccininmide (NCS), CBr 4 , N-bromosuccinimide (NBS), N-iodosuccinimide (NIS)], can trap zwitterionic intermediate 31 to provide the corresponding 2-chloro, 2bromo, 2-iodo aniline derivatives 32e. 46 Biju and co-workers reported that MCRs of arynes with tertiary aromatic amines and carbon dioxide formed zwitterionic intermediate 33, which could undergo either N→O alkyl or aryl group migration to generate anthranilic acid derivatives (Scheme 12).…”
Section: Account Syn Lettmentioning
confidence: 99%
“…The use of sulfuryl fluoride SO2F2 for the synthesis of aryl sulfonyl fluorides was reported by the group of Kim [31]. They performed a multicomponent reaction (MCR) in-…”
Section: Sulfonyl Fluorides Synthesis From Arynesmentioning
confidence: 99%
“…The use of sulfuryl fluoride SO 2 F 2 for the synthesis of aryl sulfonyl fluorides was reported by the group of Kim [31]. They performed a multicomponent reaction (MCR) involving the in-situ generation of aryne precursors from (trimethylsilyl) phenyl trifluoromethanesulfonate, secondary amines and SO 2 F 2 .…”
Section: Sulfonyl Fluorides Synthesis From Arynesmentioning
confidence: 99%
“…(Scheme 1C). [ 10 ] Despite these advances, access to various arenesulfonyl fluoride from inexpensive and wildly available starting material by a practical and mild method is still highly desired.…”
Section: Background and Originality Contentmentioning
confidence: 99%